Numerical investigation elucidating effects of microstructure on the transient thermomechanical phenomena during laser impact welding. (July 2022) - Gleason, Glenn; Sunny, Sumair; Mathews, Ritin; Malik, Arif
Abstract: Transient thermomechanical phenomena such as extreme plastic strains and temperature spikes that occur during laser impact welding are impractical to experimentally observe given the sub-microsecond duration of the joining process. Thus, computational models are necessary to study in-situ behavior along the weld interface. While researchers have utilized computational models for such investigations, this work elucidates the specific influence of microstructure-level modeling that captures the associated inhomogeneity/anisotropic effects at smaller scales. An aluminum 1100-H19 flyer and a stainless steel 304-O target foil are modeled using an Eulerian framework to simulate cases with and without microstructure consideration during laser impact welding of dissimilar metallic foils. When considering microstructure modeling, variations in flow stress reveal intermittently elevated temperatures along the weld interface due to concentrations of shock pressure at relatively small grains; however, they are not found to be a significant source of instability initiating or influencing the joint formation. Grain refinement and material hardening are suggested within a 10 μm-thick zone of the flyer near the weld interface, while severe plastic deformation in the target indicates possible martensitic phase transformation. Grain boundary sliding driven by variations in yield surfaces among individual grains gives rise to relatively higher collision velocity. Consequently, higher plastic strain rates along with greater amounts of plastic heat dissipation at the interface result in increased material jetting at higher temperatures. Alternating transient shear stresses are predicted in each model, though the inhomogeneous model predicts the brief appearance of a concentrated shear zone in the rebound region which is not seen in the homogeneous model. This work illuminates correlations between microstructure and transient phenomena during laser impact welding of dissimilar metallic foils, thus demonstrating a numerical modeling approach extensible to numerous other impact welding processes that complete within a very short time span.